Recurrence of Scaphoid Stress Fracture: A Case Report - Johnson, Nick A.; Kurien, Tom; Horton, Tracy C. (Journal of Wrist Surgery, 2021)
Background Scaphoid stress fractures are rare and typically present in young, elite male athletes. Due to the infrequency in which these injuries are encountered, the optimum management is not established.Case Description We present the case of a 20-year-old male gymnast with bilateral stress fractures of the scaphoid waist. Following conservative treatment, clinical and radiological signs of union were seen bilaterally. Eight months after return to normal activities, a unilateral recurrence of the stress fracture occurred. This was successfully treated with internal fixation and bone grafting.Literature Review Scaphoid stress fractures are most frequently seen in gymnasts but also occur in participants of other sports involving repetitive loading of an extended wrist. This action conveys force predominantly through the waist of the scaphoid. Most case studies have reported high union rates, whether treated operatively or conservatively, and the patients returned to high-level sport with no further problems. Stress fracture recurrence has been reported in other bones such as the metatarsal and tibia but never before in the scaphoid. Our case is unusual in that the patient suffered ongoing problems due to a recurrence of the scaphoid stress fracture after returning to normal activities.Clinical Relevance Clinicians should be aware that scaphoid stress fracture recurrence can occur, counsel patients accordingly, and remain vigilant after apparent union. We would recommend early fixation to allow a quicker return to function and prevention of recurrence.
Keywords: scaphoid fractures; stress fracture; recurrent stress fracture; scaphoid nonunion